Konsep Ta’dib dan Relevansinya Terhadap Pendidikan Karakter Anak Usia Dini - Nidaan Khafiyya (Taqaddumi: Journal of Quran and Hadith Studies, 2022)
This study discusses the concept of ta'dib and its relevance to children's character education. Ta'dib is an educational concept that aims to produce civilized human beings. Ta'dib is an intellectual, spiritual, and social education for teenagers and adults. Character education of children is an urgent matter that needs attention. Character education is not only about making children behave well, but more about forming good thoughts, characters, and behaviors so that children succeed. Data collection in this study was carried out by reviewing and digging up several relevant journals, books and literature. This research is a descriptive qualitative analysis, which attempts to describe the concept of ta'dib and its relevance to early childhood character education. The relevance of the concept of ta'dib with early childhood character education is aimed at producing intelligent and intelligent children, having noble character, having physical faith and piety, present in daily behavior.